Implementation of Statistical Control Processes in Benghazi's Food Industry - Abdelwanis , Naji; Alkshir , Asma; Al-Amami , Eman; AlWarfali , Sondos; Badi , Abdelaziz (Scientific Journal of University of Benghazi, 2024)
Quality control is a crucial aspect of any organization aiming to reach a high-quality level by providing products or services that satisfy customer needs. Control charts are among the most effective tools used to detect the occurrence of defects in the manufacturing process so they can be fixed before being delivered to the customers. This paper aims to assess the filling machine's performance in the Al-WAHA factory. In this investigation, a control chart and process capacity were implemented. Comprehensive details on the control chart and process capacity are discussed, along with an overview of the literature on related subjects. 33 samples of 800-gram jars' worth of data were examined. The metrics for performance were computed. Through the control charts S and X, it was found that there were ten out-of-control samples in the mean chart (3, 4, 6, 7, 8, 10, 21, 23, 32, 33) and one observation in the variance chart (30) due to assignable reasons. After excluding the samples that caused the variance in the mean chart, the control charts. Both the S and X charts are within the control limits. Filling process capacity = 0.59, the process is unable to meet the specifications, and about 23.48% of the fillings are above 810 grams and 1.51% are below 790 grams. The CPK value describes the process as decentralized.